Controls on post-High Park Fire channel response, South Fork Cache la Poudre Basin, Colorado - Shahverdian, Scott M., author; Rathburn, Sara, advisor; Wohl, Ellen, committee member; Nelson, Peter, committee member (Colorado State University. Libraries, 2015)
Post-fire basin sediment yield is the product of multiple erosional processes operating at multiple spatial scales and in different process domains. Most post-fire erosion response studies have focused on the hillslope scale, yet land management decisions and post-fire treatments are addressed at the watershed scale. The goal of this study was to evaluate how the channel network contributes to the production, transport, and storage of sediment by monitoring post-fire channel response. A better understanding of channel production, transport, and storage of sediment post-fire is required in order to predict basin scale sediment yields and make informed management decisions. Two perennial headwater streams and two ephemeral tributaries of the South Fork Cache la Poudre River were monitored in two severely burned basins in the 2012 High Park Fire burn area of northern Colorado. The basins were either completely or partially mulched with agricultural straw and wood mulch during June 2013. Repeat cross section and longitudinal profile surveys were performed to evaluate event-driven changes. The dominant response in both basins post-fire was net degradation. Steep channel slopes promoted channel incision with no significant overbank deposition, indicating that the channel network was a substantial source of sediment and an efficient transporter of hillslope sediment. In 2013, six storms exceeded the 30 minute maximum intensity 10 mm hr⁻¹ associated with hillslope sediment production while in 2014 two storms exceeded this threshold. Perennial channel response in 2014, measured by mean bed elevation change at cross sections, ranged from -20 to +17 cm, but most cross sections experienced changes between 0-3 cm. Channel response was uncorrelated with channel slope, channel slope*contributing area product, or width to depth ratio. Ephemeral channels showed an alternating cycle of aggradation and degradation on the order of 0-3 cm per event, as well as a scour and fill response during storm events. Scour and fill often resulted in minimal net changes to channel geometry, suggesting that the channel was an important temporary source and sink of sediment and that post-fire peak flow calculations must account for event-based scour. In 2013, suspended sediment concentrations in the South Fork Cache la Poudre exceeded 2500 mg L⁻¹ 12 times, and exhibited a threshold response when MI₃₀ exceeded 10 mm hr⁻¹. In 2014, suspended sediment concentrations exceeded 1500 mg L⁻¹ once, and a MI₃₀ of 40 mm hr⁻¹ was insufficient to cause values to exceed 1500 mg L⁻¹. Post-fire suspended sediment concentrations from the South Fork Cache la Poudre River indicate that hillslopes were the primary source of suspended sediment. Where the straw mulch was retained on hillslopes, it was effective at limiting erosion. The channel network was largely resistant to change during the second year of post-fire monitoring due to the influence of a >200 year storm that occurred in September 2013. Following this storm, the channel network acted primarily to transport sediment rather than produce sediment. Sediment connectivity within the channel network was high in each basin due to steep channel slopes, but the development of an alluvial fan at each basin outlet as well as the morphology of the South Fork Cache la Poudre at each confluence suggest differences in the sediment delivery from each basin to downstream reaches. Sediment connectivity from the hillslopes to the channel network and along the channel network must be addressed in post-fire studies when predicting or interpreting post-fire basin sediment yields. Furthermore, assessing sediment connectivity is a useful tool for land managers making post-fire erosion mitigation decisions.